2019
DOI: 10.1002/rcm.8441
|View full text |Cite
|
Sign up to set email alerts
|

Ionisation bias undermines the use of matrix‐assisted laser desorption/ionisation for estimating peptide deamidation: Synthetic peptide studies demonstrate electrospray ionisation gives more reliable response ratios

Abstract: Rationale Although mass spectrometry (MS) is routinely used to determine deamination in peptide mixtures, the effects of the choice of ionisation source have not yet been investigated. In particular, matrix‐assisted laser desorption/ionisation (MALDI) has become a popular tool with which to measure levels of glutamine deamidation in ancient proteins. Here we use model synthetic peptides to rigorously compare MALDI and electrospray ionisation (ESI). Methods We used two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…We assessed the authenticity of the sequences by estimating the extent of deamidation. This is a rather crude but usually effective measure of the extent of overall degradation -not necessarily of age (Schroeter and Cleland, 2016;Simpson et al, 2019Simpson et al, , 2016Welker et al, 2016). In our case, we obtained results that were internally consistent: in EVA_C (heavily handled) all collagens appeared to be "ancient" and all keratins "modern", while in EVA_M16747 (not heavily handled but with a century-long post-excavation history), all collagens and all keratins appeared "ancient".…”
Section: Discussionsupporting
confidence: 67%
“…We assessed the authenticity of the sequences by estimating the extent of deamidation. This is a rather crude but usually effective measure of the extent of overall degradation -not necessarily of age (Schroeter and Cleland, 2016;Simpson et al, 2019Simpson et al, , 2016Welker et al, 2016). In our case, we obtained results that were internally consistent: in EVA_C (heavily handled) all collagens appeared to be "ancient" and all keratins "modern", while in EVA_M16747 (not heavily handled but with a century-long post-excavation history), all collagens and all keratins appeared "ancient".…”
Section: Discussionsupporting
confidence: 67%
“…A recent study [Simpson et al, 2019] demonstrated that MALDI technique underestimates peptides with E in peptide mixtures containing Q and E substitutions that could potentially result in the systematic overestimation of q , i.e. remaining Q.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study (Simpson et al, 2019) demonstrated that MALDI technique underestimates peptides with E in mixtures containing Q and E substitutions that could potentially result in the systematic overestimation of q, i.e. remaining Q.…”
Section: Relative Rates Of Deamidationmentioning
confidence: 99%